A brief overview to give a new perspective on mole drainage - Muhittin Yağmur Polat; Mehmet Emin Bilgili (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2023)
Draining excess water from the soil is the general purpose of drainage. Thus, soil protection is provided and product losses are prevented. Mole drainage consists of underground galleries that act as piped drainage. This type of drainage is mostly used successfully in clay, organic, and highly cohesive soils. It is used successfully in areas with high groundwater, during the improvement of salty and sodium soils. The biggest benefit of mole drainage is cheap and economical. In the mole drainage method, tunnels are opened under the tillage depth with a torpedo-shaped piece at the end of a foot extending under the soil. These tunnels are called mole drains. In the mole drainage method, the channels are built with mole drain plows and subsoilers. In order to benefit more effectively from mole drainages, parameters such as suitable working width, working depth and slope must be finely adjusted. For this, modern alternatives such as GPS and laser positioning systems can be used.